CONGENITAL METHAEMOGLOBINEMIA – A RARE CASE OF CYANOSIS - DR. NOORUL AMEEN; DR. S. HABEEB AHMED ABDUL KAIYOOM; DR. AAFRIN SHABBIR (International Journal of Pharma and Bio Sciences, 2014)
Cyanosis, both peripheral and central, is a very common and important clinical finding seen in many disorders of the cardiovascular and respiratory system. But in addition to the commonly seen causes, there are certain uncommon causes of cyanosis which are overlooked and seldom diagnosed. Many classes of drugs and chemical agents used in regular practice have shown to induce cyanosis in adults. Among the hereditary causes of cyanosis, congenital methaemoglobinemia is a rare cause of cyanosis seen in the absence of any cardiac or pulmonary abnormalities. Usually diagnosed in the neonatal period, most cases go undiagnosed and eventually untreated in our country, to be picked up only during adulthood. There are many subtypes of congenital methaemoglobinema, of which some are fatal while others being only mildly symptomatic. These patients go on to lead normal lives albeit with mild symptoms and obvious cyanosis. Here we present a rare case of Congenital methaemoglobinemia, untreated until he presented to us at 25 years of age. In view of absent cardiac or pulmonary abnormalities as to the cause of his cyanosis, he was thoroughly evaluated and was found to have Type 1 Congenital methaemoglobinemia. He was subsequently treated and is doing well, on a regular follow up with us as well. Type 1 congenital methaemoglobinemia is a treatable cause of cyanosis and should be suspected in all cases of cyanosis without any cardio-pulmonary abnormalities. Type 1 congenital methaemoglobinemia responds well to treatment with methylene blue. Ascorbic acid, cimetidine and hyperbaric oxygen therapy are other alternatives in the treatment of congenital methaemoglobinemia.